2010
DOI: 10.1038/ki.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide reduces proteinuria in experimental membranous nephropathy and protects against C5b-9-induced podocyte injury in vitro

Abstract: Membranous nephropathy is a major cause of nephrotic syndrome in adults where podocyte injuries were found to mediate the development of proteinuria. Triptolide, a major active component of Tripterygium wilfordii Hook F, has potent immunosuppressive, anti-inflammatory and antiproteinuric effects. To study its antiproteinuric properties, we established an experimental rat model of passive Heymann nephritis and a C5b-9 injury model of podocytes in vitro. Treatment or pretreatment with triptolide markedly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 40 publications
2
87
1
Order By: Relevance
“…Triptolide attenuates renal interstitial fibrosis in rats with unilateral ureteral obstruction (Yuan et al, 2011). Triptolide can dramatically attenuate albuminuria and renal lesion accompanied with dyslipidemia and obesity in db/db diabetic mice (Gao et al, 2010), and in experimental membranous nephropathy, triptolide decreases reactive oxygen species and p38 MAPK (Chen et al, 2010). Triptolide protects podocytes from puromycin aminonucleoside-induced injury in vivo and in vitro (Zheng Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triptolide attenuates renal interstitial fibrosis in rats with unilateral ureteral obstruction (Yuan et al, 2011). Triptolide can dramatically attenuate albuminuria and renal lesion accompanied with dyslipidemia and obesity in db/db diabetic mice (Gao et al, 2010), and in experimental membranous nephropathy, triptolide decreases reactive oxygen species and p38 MAPK (Chen et al, 2010). Triptolide protects podocytes from puromycin aminonucleoside-induced injury in vivo and in vitro (Zheng Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PG490-88 prolongs renal allograft survival in monkeys (Chen et al, 2006). Triptolide reduces cyst growth in autosomal dominant polycystic kidney disease (ADPKD) (Leuenroth et al, 2007), decreases experimental membranous nephropathy (Chen et al, 2010) and podocyte injury (Zheng et al, 2008), and attenuates diabetic nephropathy in rodents (Gao et al, 2010). Triptolide decreases interstitial fibrosis in a model of unilateral kidney obstruction (Yuan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in vitro experiments have indicated that triptolide can stabilize the skeleton mycin aminonucleoside (PAN) to podocyte, and when podocyte is damaged, triptolide can reverse the damage of podocytes and recover the skeleton structure of podocytes and the expression of relevant molecules [8]. Currently, the influence of triptolide on podocytes is considered to be an important factor for the decrease of urine protein of patients with glomeru-lonephritis [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, in vitro experiments have indicated that triptolide can stabilize the skeleton mycin aminonucleoside (PAN) to podocyte, and when podocyte is damaged, triptolide can reverse the damage of podocytes and recover the skeleton structure of podocytes and the expression of relevant molecules [8]. Currently, the influence of triptolide on podocytes is considered to be an important factor for the decrease of urine protein of patients with glomeru-lonephritis [8,9]. With the research on the influence of glomerular podocytes on proteinuria production, people have recognized that for some diseases of the renal glomeruli which are characterized in a great quantity of proteinuria and accompanied by the damage to podocyte such as minute lesion, focal segmental glomerulo-sclerosis and membranous nephropathy, TW works well on reducing proteinruia to all the above diseases [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation